EKLESIOLOGI KEMURIDAN DALAM KAJIAN TEKS GAUDIUM ET SPES ART. 1 - Petrus Canisius Edi Laksito (Bahasa Indonesia, 2019)
The First Pastoral Consultation of the Diocese of Surabaya held on November 26th-28th 2009 proposed The Basic Direction of the Diocese of Surabaya 2010-2019, which is stating the desire of the Church of the Diocese of Surabaya to be“a communion of Christ’s disciples, which is more and more maturing in faith, convivial, full of service and missionary”. The Second Pastoral Consultation held on October 18th-20th 2019, keeping this purpose statement for the next 10 years inThe Basic Direction of the Diocese of Surabaya 2020-2030, thus confirms the significancy of an “Ecclesiology of Discipleship” for the formation of the people of the Diocese. This paper wants to propose a study regarding this ecclesiology based on the document of the Second Vatican Council, i.e. The Pastoral Constitution Gaudium et Spes, art. 1. Being a Pastoral Constitution on the Church in the modern world, Gaudium et Spes, opened with a statement regarding the unity of the followers of Christ and the men of this age, would be fundamentally authoritative and enlightening for reflecting the vocation of the local Church of Surabaya as “a communion of the disciples of Christ” to become aware of her mission for the world (ad extradimension), while she is, as a communion of the faith (ad intra dimension), journeyingtowards eternal unity with the God